The role of electrode wettability in electrochemical reduction of carbon dioxide. Issue 35 (16th July 2021) - Li, Mengran; Idros, Mohamed Nazmi; Wu, Yuming; Burdyny, Thomas; Garg, Sahil; Zhao, Xiu Song; Wang, Geoff; Rufford, Thomas E.
Abstract : This review provides an in-depth analysis of essential role of electrode wettability in improving CO2 electrochemical reduction. Abstract : The electrochemical reduction of carbon dioxide (CO2 RR) requires access to ample gaseous CO2 and liquid water to fuel reactions at high current densities for industrial-scale applications. Substantial improvement of the CO2 RR rate has largely arisen from positioning the catalyst close to gas–liquid interfaces, such as in gas-diffusion electrodes. These requirements add complexity to an electrode design that no longer consists of only a catalyst but also a microporous and nanoporous network of gas–liquid–solid interfaces of the electrode. In this three-dimensional structure, electrode wettability plays a pivotal role in the CO2 RR because the affinity of the electrode surface by water impacts the observed electrode reactivity, product selectivity, and long-term stability. All these performance metrics are critical in an industrial electrochemical process. This review provides an in-depth analysis of electrode wettability's role in achieving an efficient, selective, and stable CO2 RR performance. We first discuss the underlying mechanisms of electrode wetting phenomena and the foreseen ideal wetting conditions for the CO2 RR. Then we summarize recent advances in improving cathode performance by altering the wettability of the catalyst layer of gas-diffusion electrodes. We conclude the review by discussing the current challenges and opportunities to develop efficient and selective cathodes for CO2 RR at industrially relevant rates. The insights generated from this review could also benefit the advancement of other critical electrochemical processes that involve multiple complex flows in porous electrodes, such as electrochemical reduction of carbon monoxide, oxygen, and nitrogen.